A Cross-Cultural Investigation of New Product Strategies for Technological and Design Innovations. Issue 1 (March 2014) - Griffith, David A.; Rubera, Gaia
Although design and technological innovations are conceptually distinct and require significantly different resource investments by the firm, little is known about how differing strategies employed in relation to these new products influence changes in market share across national cultures. In this study, the authors provide insights into how technological and design product innovations and product portfolio breadth strategies influence changes in market share within 26 technological and 12 design innovations across 17 firms operating in eight European countries. The results indicate that the positive effect of design innovation on changes in market share strengthens as individualism and indulgence increase, whereas the positive relationship between technological innovations and market share is weakened as uncertainty avoidance and indulgence increase. In addition, the positive relationship between design product portfolio breadth strategies and changes in market share is strengthened as individualism and indulgence increase but is weakened as uncertainty avoidance increases, whereas the positive relationship between technological product portfolio breadth and changes in market share is strengthened as individualism increases. The authors discuss the theoretical and managerial implications of the findings.